Taking Back the Narrative: Gendered Anti-Blackness in Predominantly White Schools of Social Work. Issue 4 (November 2022) - F. Jackson, Kelly; Mitchell, Felicia M.; Ogbonnaya, Ijeoma Nwabuzor; Mackey, Cynthia; Crudup, Chandra; Carver, Ann Turnlund
Black women scholars have and continue to make significant contributions to the social work profession; however, their experiences within the profession are mostly absent in the literature. In general, Black women face numerous challenges within schools of social work. Black women scholars endure a compound form of anti-Blackness in higher education known as gendered anti-Blackness due to their multiple marginalized statuses associated with race and gender. This study examined the phenomenon of gendered anti-Blackness as experienced in academia by a diverse group of Black and mixed Black faculty and PhD students. We intentionally utilized a new methodology, Black Feminist Polyethnography, to provide an affirming and communal space for us to dialogically reflect on our collective experiences of gendered anti-Blackness in predominantly white schools of social work. Our findings uncovered six Black woman-centered proverbs that symbolize the ways we collectively thrive as scholars despite gendered anti-Blackness.